KEY ISSUES IN THE MANAGEMENT OF THE HUMANITARIAN AID DISTRIBUTION PROCESS DURING AND POST-DISASTER IN MALAYSIA - Mohd, Suzila; Fathi, Mohamad Syazli; Harun, Aizul Nahar; Omar Chong, Noraini (PLANNING MALAYSIA, 2018)
The humanitarian aid distribution process is a broad activity for helping disaster victims at the right time, with the right needs and at the right place during a disaster. However, there are always issues that could interfere with the humanitarian aid distribution process such as cases of food redundancy, uneven distribution of food supply to disaster victims, food insecurity issues, and volunteers’ redundancy during and post disasters. These issues prove that there are weaknesses in managing the humanitarian aid distribution process within disaster management teams. Generally, these issues should be taken care of when the disaster management team was formed either from government agencies or non-governmental organizations (NGOs). Both work as the supporting team in giving aids and helping the disaster victims. Therefore, this research reviews the key issues in the humanitarian aid distribution process in Malaysian disaster management. Key findings show that there is no standard operating procedure (SOP) to explain the roles and responsibilities of NGOs that can be used by Government agencies to coordinate NGO contributions to a supporting team. There are five (5) categories of issues that can have a negative impact on the humanitarian aid distribution process and the disaster victims. The issues are information, communication, collaboration, cooperation, and coordination. All disaster management teams should emphasize these issues as they affect effectiveness in dealing with the humanitarian aid distribution process.